Burn baby burn - Medina, Meg (Candlewick Press, 2016)
Nora Lopez is seventeen during the summer of 1977, when New York is besieged by arson, a massive blackout, and a serial killer named Son of Sam. Meg Medina transports us to a time when tempers and temperatures ran high to share the story of a young woman who discovers that the greatest dangers are often closer than we like to admit.